Copy number variation in a hospital‐based cohort of children with epilepsy. Issue 2 (8th May 2017) - Vlaskamp, Danique R. M.; Callenbach, Petra M. C.; Rump, Patrick; Giannini, Lucia A. A.; Dijkhuizen, Trijnie; Brouwer, Oebele F.; van Ravenswaaij‐Arts, Conny M. A.
Summary: Objective: To evaluate the diagnostic yield of microarray analysis in a hospital‐based cohort of children with seizures and to identify novel candidate genes and susceptibility loci for epilepsy. Methods: Of all children who presented with their first seizure in the University Medical Center Groningen (January 2000 through May 2013) (n = 1, 368), we included 226 (17%) children who underwent microarray analysis before June 2014. All 226 children had a definite diagnosis of epilepsy. All their copy number variants (CNVs) on chromosomes 1–22 and X that contain protein‐coding genes and have a prevalence of <1% in healthy controls were evaluated for their pathogenicity. Results: Children selected for microarray analysis more often had developmental problems (82% vs. 25%, p < 0.001), facial dysmorphisms (49% vs. 8%, p < 0.001), or behavioral problems (41% vs. 13%, p < 0.001) than children who were not selected. We found known clinically relevant CNVs for epilepsy in 24 of the 226 children (11%). Seventeen of these 24 children had been diagnosed with symptomatic focal epilepsy not otherwise specified (71%) and five with West syndrome (21%). Of these 24 children, many had developmental problems (100%), behavioral problems (54%) or facial dysmorphisms (46%). We further identified five novel CNVs comprising four potential candidate genes for epilepsy: MYT1L, UNC5D, SCN4B, and NRXN3 . Significance: The 11% yield in our hospital‐based cohort underscores the importance of microarray analysis in diagnostic evaluation of children with epilepsy.